Global change, novel ecosystems and the ecological restoration of post‐industrial areas: The case of a former brown coal mine in Søby, Denmark. Issue 3 (12th September 2021) - Conradi, Timo; Henriksen, Maria V.J.; Svenning, Jens‐Christian
Abstract: Questions: Can multi‐decadal vegetation changes in a decommissioned brown coal mine be attributed to global‐change forcing? Given novel drivers of community assembly and ongoing global change, what are sensible restoration goals and strategies for large post‐industrial areas? Location: A decommissioned brown coal mine near Søby, central Denmark (56°01′45′′ N, 9°04′4′′ E). Methods: We resurveyed the plant communities of the mine 31 years after an initial survey. Changes in the prevalence of exotic species and species indicator values for environmental conditions were used to link the observed vegetation changes to global change factors. Results: The plant communities, including their unmined reference sites, changed over the 31‐year period toward plant communities with higher proportions of exotics, nitrophilous, warmth‐ and moisture‐indicating species, and species of low foraging quality for deer. The changes are consistent with the novel drivers of community assembly at the site, such as the introduction of exotic species, increased nitrogen deposition, elevated temperatures, steadily increasing groundwater level post mining, and the massive comeback of red deer. Conclusions: The global‐change forcing of novel plant communities suggests that it is becoming increasingly difficult to restore historical references. It may thus be more sensible to acknowledge novelty and adopt an open‐ended approach for the restoration of this and similar post‐industrial areas, e.g. using rewilding principles to promote biodiverse self‐sustaining ecosystems. Abstract : This study illustrates a novel ecosystem under development in a decommissioned coal mine. Thirty years after a first survey we found numerous changes in the species composition of the mine that we attributed to global change drivers, including more warmth‐ and nutrient‐demanding species and an abundant establishment of exotic species. We discuss implications for choosing restoration strategies